The Image of Horse in Antara Poetry - Bsharat, Khdair Ali (Journal of Arabic Language Sciences and Literature, 2023)
The study examines the legendary symbols of the Persians, and their association with references such as the groomed animal, motherhood, fertility or mountain, as sometimes depicted by the poet by the star, the sky’s height and stars such as sun and gemini. The research painted a picture of the man who adores his owner, fighting to protect him, and equated it with his beloved Abla, who has many women’s qualities